TARDBP mutations in a cohort of Italian patients with Parkinson’s disease and atypical parkinsonisms - Tiloca, Cinzia; Goldwurm, Stefano; Calcagno, Narghes; Verde, Federico; Peverelli, Silvia; Calini, Daniela; Zecchinelli, Anna Lena; Sangalli, Davide; Ratti, Antonia; Pezzoli, Gianni; Silani, Vincenzo; Ticozzi, Nicola (Frontiers in Aging Neuroscience, 2022)
Background Aggregates of TAR DNA-binding protein of 43 kDa (TDP-43) represent the pathological hallmark of most amyotrophic lateral sclerosis (ALS) and of nearly 50% of frontotemporal dementia (FTD) cases but were also observed to occur as secondary neuropathology in the nervous tissue of patients with different neurodegenerative diseases, including Parkinson’s disease (PD) and atypical parkinsonism. Mutations of TARDBP gene, mainly in exon 6 hotspot, have been reported to be causative of some forms of ALS and FTD, with clinical signs of parkinsonism observed in few mutation carriers. Methods Direct DNA sequencing of TARDBP exon 6 was performed in a large Italian cohort of 735 patients affected by PD (354 familial and 381 sporadic) and 142 ones by atypical parkinsonism, including 39 corticobasal syndrome (CBS) and 103 progressive sopranuclear palsy (PSP). Sequencing data from 1710 healthy, ethnically matched controls were already available. Results Four TARDBP missense variants (p.N267S, p. G294A, p.G295S, p.S393L) were identified in four patients with typical PD and in two individuals with atypical parkinsonism (1 CBS and 1 PSP). None of the detected mutations was found in healthy controls and only the variant p.N267S was previously described in association to idiopathic familial and sporadic PD and to CBS. Conclusions In this study we provide further insight into the clinical phenotypic heterogeneity associated with TARDBP mutations, which expands beyond the classical ALS and FTD diseases to include also PD and atypical parkinsonism, although with a low mutational frequency, varying considerably in different Caucasian populations. In addition, our study extends the spectrum of TARDBP pathogenetic mutations found in familial and sporadic PD.